2021
DOI: 10.4018/ijicthd.2021070102
|View full text |Cite
|
Sign up to set email alerts
|

Telecommunication Network Performances and Evaluation of Radio Frequency Electromagnetic Radiation

Abstract: The ongoing mobile communication technology intensification had occasioned the inevitable multiplications in the ratio of the radio frequency base service stations which had raised public consciousness over the considerable health hazards of the radioactive emissions from the communication systems. The current paper analysed the sequences of electromagnetic field measurements performed on the selected three states in the North West Nigeria in order to establish the compliance of radiation levels of cellular ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Biological consequences could include burns, chemical polarization (Ugochukwu ,(Ugochukwu Okwudili Matthew et al, 2022), and muscle relaxation as induced by a diathermy device in medical surgery (Liu & Liu, 2018). As a significant step in maintaining the sustainability of the natural ecosystem, numerous countries and regulatory organizations, such as the International Commission on Non-Ionizing Radiation Protection(ICNIRP), have set safety limits to checkmate electromagnetic field exposures to a non-thermal intensity (Jazuli S Kazaure, Matthew, Okafor, & Okey, 2021),(Jazuli Sanusi . It has been demonstrated that the non-thermal impacts of EMR affect a biological organism's systems, causing organic processes to alter the bodies regular functioning, including the immunological system, endocrine, sexual, and nervous systems, to be disrupted (Azab, Khalat, Ebrahim, & Albasha, 2018), (Samarth, Kumar, Matsumoto, & Manda, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Biological consequences could include burns, chemical polarization (Ugochukwu ,(Ugochukwu Okwudili Matthew et al, 2022), and muscle relaxation as induced by a diathermy device in medical surgery (Liu & Liu, 2018). As a significant step in maintaining the sustainability of the natural ecosystem, numerous countries and regulatory organizations, such as the International Commission on Non-Ionizing Radiation Protection(ICNIRP), have set safety limits to checkmate electromagnetic field exposures to a non-thermal intensity (Jazuli S Kazaure, Matthew, Okafor, & Okey, 2021),(Jazuli Sanusi . It has been demonstrated that the non-thermal impacts of EMR affect a biological organism's systems, causing organic processes to alter the bodies regular functioning, including the immunological system, endocrine, sexual, and nervous systems, to be disrupted (Azab, Khalat, Ebrahim, & Albasha, 2018), (Samarth, Kumar, Matsumoto, & Manda, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with network reliability, both the quantity of linked devices and the growing number of users within the communication systems have become issues of great concern (Tushar et al, 2021). Consequent upon the advancement in current mobile communication technologies (6G, 5G,4G and 3G), it is expected that the usage of mobile communications and device connectivity in the sustainable broadband regime would intensify in the nearest future(Ugochukwu , (Kazaure, Matthew, Okafor, & Okey, 2021). This device multiplicity will give rise to high data traffic which has risen exponentially due to online streaming, Internet of Things (IoT) connected data transmission, online gaming and video sharing(Ugochukwu Okwudili Matthew, Kazaure, John, & Haruna, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most crucial ways that the subscriber needs and that service providers can work to provide and gain more customers is the constant signal strength and the continuous wide coverage, and in order to guarantee what we mentioned, companies must build numerous towers and they are distributed over different areas. Each tower has a known and specific distance and constant signal strength according to the type of antennas placed on the tower and the transmitting base [4], [5]. There are numerous types of models that are used for covering, such as 2G model (UMTS 800) while 3G model (G1800) that is consider stronger signal compared to the models mentioned previously.…”
Section: Introductionmentioning
confidence: 99%